Bronze alloying practice in ancient China - Evidence from pre-qin coin analyses - Pollard, AM; Liu, R (Elsevier, 2021)
We have reviewed the published chemical analyses of the bronze coinage produced in pre-Qin China (before 221 BCE), with the aim of understanding the alloying practices which took place before these coins were cast. Conventionally it has been assumed that they were made to a ‘target composition’, by separately adding lead and tin to copper. However, by characterizing the composition of the different coin classes by trend lines rather than by calculating the average composition, we show that the majority of coins approximately fit a mixing line between two starting components – one containing copper, lead and tin (similar to the composition of bronze used to cast contemporary ritual vessels), and one containing only copper and lead. There is some archaeological evidence to support the existence of the latter as a raw material, in the form of fragments of Cu/Pb alloy broken from larger cakes, previously interpreted as primitive coinage. This proposal might have implications for how we consider the perceptions and practice of alloying processes for bronze objects in pre-Qin China.